A Program Transformation for Faster Goal-Directed Search - Lal, Akash; Qadeer, Shaz (Formal Methods in Computer-Aided Design (FMCAD), 2014)
A goal-directed search attempts to reveal only relevant information needed to establish reachability (or unreachability) of the goal from the initial state of the program. The further apart the goal is from the initial state, the harder it can get to establish what is relevant. This paper addresses this concern in the context of programs with assertions that may be nested deeply inside its call graph—thus, far away interprocedurally from main. We present a source-to-source transformation on programs that lifts all assertions in the input program to the entry procedure of the output program, thus, revealing more information about the assertions close to the entry of the program. The transformation is easy to implement and applies to sequential as well as concurrent programs. We empirically validate using multiple goal-directed verifiers that applying this transformation before invoking the verifier results in significant speedups, sometimes up to an order of magnitude. This paper received the best paper award at FMCAD 2014.
Best Paper Award